Risk factors for infant mortality in a municipality in southern Brazil: a comparison of two cohorts using hierarchical analysis Fatores de risco para mortalidade infantil em município do Sul do Brasil: comparação de duas coortes em análise hierarquizada - Hellen Geremias dos Santos; Selma Maffei de Andrade; Ana Maria Rigo Silva; Wladithe Organ de Carvalho; Arthur Eumann Mesas (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This study compared risk factors for infant mortality in 2000-2001 and 2007-2008 in Londrina, Paraná State, Brazil. Data on live births and infant deaths were linked in a single database, and a hierarchical regression model was used. Distal risk factors for infant mortality in 2000-2001 were maternal age < 20 or ≥ 35 years and lower maternal schooling. In 2007-2008, maternal age ≥ 35 or < 20 years were risk factors, while low schooling appeared as a protective factor. The following intermediate factors were associated with increased infant mortality in 2000-2001: multiple pregnancy, history of stillbirth, and insufficient number of prenatal visits, while cesarean delivery was a protective factor. Multiple pregnancy was the only intermediate risk factor in 2007-2008. All of the proximal factors were associated with higher infant mortality in 2000-2001, but only gestational age and 5-minute Apgar in 2007-2008. The risk factors for infant mortality changed from the first to the second cohort, which may be related to the expansion of social policies and primary care and changes in the reproductive and social patterns of Brazilian women. Compararam-se fatores de risco para mortalidade infantil nos anos 2000/2001 e 2007/2008 em Londrina, Paraná, Brasil. Dados sobre nascidos vivos e óbitos infantis foram vinculados em base de dados única, e usou-se análise de regressão em modelo hierárquico. No nível distal, foram de risco para mortalidade infantil, em 2000/2001, idade materna < 20 e ≥ 35 anos e escolaridade materna baixa. Em 2007/2008, idades maternas ≥ 35 e < 20 anos foram de risco, enquanto escolaridade baixa, protetora. Associaram-se à maior mortalidade infantil, no nível intermediário, em 2000/2001: gestação múltipla, filhos mortos e número insuficiente de consultas pré-natal, enquanto cesariana foi fator protetor. Em 2007/2008, apenas gestação múltipla foi de risco. Todos os fatores proximais associaram-se à maior mortalidade infantil em 2000/2001 e, em 2007/2008, apenas idade gestacional e Apgar no quinto minuto. Houve mudanças nos fatores de risco para a mortalidade infantil nos biênios analisados, o que pode estar relacionado à ampliação de políticas sociais e de ações básicas de saúde, e a modificações no padrão reprodutivo e social das mulheres.